Alfred Adler and Viktor Frankl: The meaning of life’s speech - Maurial Chávez, Iván (2009)
Logotherapy and Adler‘s psychology are related since its origins, as an opposition of the classic psychoanalysis’s view. Nevertheless, the ideological differences between their creators just left an appearance of opposition instead of the one of affinity. In the present article the author tries to demonstrate that the theoretical disagreements between Adler and Frankl were real but superficial and their observations are supplementary trying to introduce us a human man as a being in constantly search of meaning. In order to formulate my proposal, I overall appeal to Frankl’s books and other well-known authors in the Adler’s psychology. The presentation of the texts will give the validity of mi purpose.